Phenylpropanoid and Iridoid Glucosides from the Whole Plant of Hemiphragma heterophyllum and Their alpha-Glucosidase Inhibitory Activities - Li, Yan-Hong; Dai, Jia-Meng; Yang, Cui; Jiang, Meng-Yuan; Xiong, Yong; Li, Yu-Kui; Li, Hong-Rui; Tian, Kai; Huang, Xiang-Zhong (Planta Medica, 2020)
Three phenylpropanoid glucosides (1 – 3) and one iridoid glucoside (11), together with eleven known glucosides, were isolated from the ethanol extract of the whole plant of Hemiphragma heterophyllum. Their structures were elucidated by means of 1D and 2D NMR spectroscopy, HRMS, and chemical methods. All compounds except 11 and 13 – 15 showed varying degrees of α-glucosidase inhibitory activity. Compounds 5, 9, and 12 were marginally active in the bioassay, while compounds 1 – 4, 6 – 8, and 10 exhibited appreciable inhibitory activity with an IC50 value of 33.6 ~ 83.1 µM, which was much lower than that of the positive control acarbose (IC50 = 310.8 µM).
Keywords: Hemiphragma heterophyllum; Scrophulariaceae; phenylpropanoid glucosides; iridoid glucosides; α-glucosidase inhibitor activity